Interventional Therapy Versus Medical Therapy for Secundum Atrial Septal Defect: A Systematic Review (Part 2) for the 2018 AHA/ACC Guideline for the Management of Adults With Congenital Heart Disease. Issue 14 (2nd April 2019) - Oster, Matthew; Bhatt, Ami B.; Zaragoza-Macias, Elisa; Dendukuri, Nandini; Marelli, Ariane
Abstract : Secundum atrial septal defect (ASD) is the most common adult congenital heart defect and can present with wide variation in clinical findings. With the intention of preventing morbidity and mortality associated with late presentation of ASD, consensus guidelines have recommended surgical or percutaneous ASD closure in adults with right heart enlargement, with or without symptoms. The aim of the present analysis was to determine if the protective effect of secundum ASD closure in adults could be qualified by pooling data from published studies. A systematic review and meta-analysis were performed by using EMBASE, MEDLINE (through PubMed), and the Cochrane Library databases to assess the effect of secundum ASD percutaneous or surgical closure in unoperated adults ≥18 years of age. Data were pooled across studies with the DerSimonian-Laird random-effects model or a Bayesian meta-analysis model. Between-study heterogeneity was assessed with Cochran's Q test. Bias assessment was performed with the Newcastle-Ottawa Scale and the Cochrane Risk of Bias Tool, and statistical risk of bias was assessed with Begg and Mazumdar's test and Egger's test. A total of 11 nonrandomized studies met the inclusion criteria, contributing 603 patients. Pooled analysis showed a protective effect of ASD closure on New York Heart Association functional class and on right ventricular systolic pressure, volumes, and dimensions. Two additional studies comprising 652 patients were reviewed separately for mortality outcome and primary outcome of interest because they did not meet the inclusion criteria. Those studies showed that ASD closure was associated with a weak protective effect on adjusted mortality rate but no significant impact on atrial arrhythmias in patients >50 years of age. Across all studies, there was significant heterogeneity between studies for nearly all clinical outcomes. The overall body of evidence was limited to observational cohort studies, the limitations of which make for low-strength evidence. Even within the parameters of the included studies, quality of evidence was further diminished by the lack of well-defined clinical outcomes. In conclusion, pooled data analysis on the impact of secundum ASD closure in adults was notably limited because of the lack of randomized controlled trials in patients with only secundum ASD. The few cohort studies in this population demonstrated improvement in functional status and right ventricular size and function as shown by echocardiogram. However, our findings suggest that at the time of this publication, insufficient data are available to determine the impact of ASD repair on mortality rate in adults. Abstract : Supplemental Digital Content is available in the text.